Employment of Set Operations to Improve LMP Assessments Design and Implementation - Malek Khalaf Albezuirat; Rosmaini Ahmad; Muhammad Iqbal Hussain; Falah Mustafa Al-Saraireh; Asia Khalaf Albzeirat (SEISENSE Journal of Management, 2019)
Objective - This paper aims to provide a new mathematical model for the construction of assessment tools for Lean Manufacturing Practices (LMP) through the integration process with the set operations. This study also strives to develop key elements to enhance the effectiveness of LMP assessments and their impact through mathematical interrelationship.